PENINGKATAN SIKAP KEDISIPLINAN DALAM KEGIATAN BELAJAR MENGAJAR SISWA DI SD AL MA’SOEM BANDUNG - Rakanita Dyah Ayu Kinesti; Indriani Noor Agustin; Farida Nur Wahidah; Eka Miftakhussa'adah; Naila Darojatil Ulya; Khalimatus Sa'diyyah (Jurnal Pendidikan Dasar, 2021)
Education is the main thing. In addition, discipline must always go hand in hand with education. Discipline is getting lost and bad attitudes are now considered normal and natural, one of which is cheating during exams. The increasing number of cases, especially among elementary schools, must be eradicated immediately so that cheating does not become a habit. Because if from elementary school they are not disciplined and often cheat, then adults will form individuals who are easy to lie and behave badly. Al-Ma'soem Elementary School has its own way to overcome this problem, including upholding high discipline by making rules strict and upholds a disciplined attitude and does not abandon the values ​​of Islamic education. Likewise in the provision of sanctions for students who violate these rules. Namely through the provision of sanctions against each student who violates the discipline, including the provision of sanctions in the form of points according to the level of violation. This method is able to change student behavior for the better and disciplined, of course, as well as providing appropriate and correct sanctions, where there is no violence or things that are not good but provide a tremendous deterrent effect for students so that they are afraid to repeat their mistakes again.